Cropping sequences and no-till quality indicators in the Middle Plateau of Rio Grande do Sul - Passinato, Jardel Henrique; Brenner, Mateus da Silva; Campos, Ben-Hur Costa de; Kunz, Karine Mariele; Tornquist, Carlos Gustavo; Cruz, Sandra Meinen da; Tramontini, Adriano Scholze (Revista de Ciências Agroveterinárias, 2020)
The no-tillage system (SPD) brings together the largest complex of conservation technologies for tropical and subtropical soils, however many producers are partially adopting these precepts, enhancing its degradation. The objective of this work was to evaluate the quality of SPD in a locality, located in the Middle Plateau of Rio Grande do Sul, observing the current situation of soil management and agricultural plots in the region conducted under SPD. Land use monitoring was carried out at Linha Cristal, located in the city of Selbach, RS, as well as the evaluation of agricultural plots that represented the different managements observed there, as well as a native forest as reference. For this, the dry phytomass (DP) and the soil surface coverage rate (CR), the density (Sd), critical density (Bd) and degree of compaction (DC) of the soil were determined, in addiction to soil organic matter (SOM). Statistical analysis consisted of univariate analyzes (mean and standard deviation), while the results between the SOM and Ds levels were also submitted to regression analysis. The cultivated area showed low crop diversity in summer crops, predominating soybean (88.6%). Most of the corn in 2016/17 was destined to silage production (59%). The winter harvests were more diversified, with predominance of wheat, barley, white oats and black oats. The annual average DP added to the soil (13,147 and 11,508 kg/hectare/year) were above the minimum to maintain the SOM levels stipulated by the literature (9,000 kg/hectare/year). Farmland presented the densest 7-14 cm layer, where only one of the farmland presented Ds value lower than Dsc. There was an inverse linear correlation between Ds and MOS, where the areas containing the highest SOM contents had the lowest Ds.